2001
DOI: 10.1029/2001jd900198
|View full text |Cite
|
Sign up to set email alerts
|

El Niño‐Southern Oscillation (ENSO) influence on a Sajama volcano glacier (Bolivia) from 1963 to 1998 as seen from Landsat data and aerial photography

Abstract: Abstract. Sajama volcano, located in the Bolivian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…Our results are in accordance with our current understanding of the ENSO/glacier relationship in the Central and Tropical Andes (e.g. Arnaud et al, 2001;Favier et al, 2004;Francou et al, 2004;Vuille et al, 2008b;Veettil et al, 2014). However, we find a stronger SSTA → MB relationship than described in Vuille et al (2008b) and cannot confirm their exceptional years (1983 and 1994).…”
Section: Summary and Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our results are in accordance with our current understanding of the ENSO/glacier relationship in the Central and Tropical Andes (e.g. Arnaud et al, 2001;Favier et al, 2004;Francou et al, 2004;Vuille et al, 2008b;Veettil et al, 2014). However, we find a stronger SSTA → MB relationship than described in Vuille et al (2008b) and cannot confirm their exceptional years (1983 and 1994).…”
Section: Summary and Discussionsupporting
confidence: 70%
“…The influence of ENSO in the tropical and central Andes can be roughly summarized with prevailing warmer and drier conditions during El Niño phases, while colder and wetter conditions prevail during La Niña phases. As a result, studies dealing with ENSO's influence on tropical Andean glaciers reported a significant anti-correlation between Pacific sea-surface temperature anomalies (SSTA) and MB (Arnaud et al, 2001;Francou et al, 2004;Vuille et al, 2008b;Veettil et al, 2014). The extreme 1997/98 Niño year, for example, caused exceptional glacier melt in the outer tropics (Wagnon et al, 2001;Francou et al, 2003).…”
Section: F Maussion Et Al: Enso Influence On Shallap Glacier Cordimentioning
confidence: 99%
“…This strong interannual variability of summer precipitation has been described in a number of studies and there is a general agreement that a signi¢cant fraction of this variability is related to the El Nin ‹ o Southern Oscillation (ENSO) phenomenon (e.g. Thompson et al, 1984;Aceituno, 1988;Ronchail, 1995;Lenters and Cook, 1999;Vuille, 1999;Vuille et al, 2000a;Arnaud et al, 2001;Garreaud and Aceituno, 2001). All of these studies concluded that El Nin ‹ o years (warm phase of ENSO) tend to be dry, while La Nin ‹ a years (ENSO cold phase) are often associated with wet conditions on the Altiplano.…”
Section: Interannual Variabilitymentioning
confidence: 99%
“…This last point will be the focus of a forthcoming paper. Finally, ENSO influence on Sajama Volcano glaciers has also been highlighted by Arnaud et al (2001), showing that the snow line elevation is related primarily to precipitation and to a lesser degree to temperature.…”
Section: Regional Forcing Of the Mass Balance Interannual Variabilitymentioning
confidence: 99%